Untangling the systematic dilemma behind the roughskin spurdog Cirrhigaleus asper (Merrett, 1973) (Chondrichthyes: Squaliformes), with phylogeny of Squalidae and a key to Cirrhigaleus species - Viana, Sarah; Soares, Karla D. A. (PLOS ONE, 2023)
Cirrhigaleus comprises a small genus of rare barbel-bearing dogfish sharks with distributions in limited regions of all oceans. Generic validity and taxonomic status of some species are upon controversies by morphological and molecular evidence that often suggest reallocation of Cirrhigaleus species into the genus Squalus. Particularly, the roughskin spurdog C. asper exhibits intermediary morphological characteristics within Squalidae that requires clarification. In the present study, a phylogenetic approach was undertaken to test the correct generic placement of C. asper using novel and revised morphological characters. We performed maximum parsimony analysis of 51 morphological characters of the internal (e.g., neurocranium, clasper cartilages, pectoral and pelvic girdles) and external anatomy applied to 13 terminal taxa. Cirrhigaleus represents a valid genus and it is supported by eight synapomorphies: high number of monospondylous vertebrae; medial nasal lobe supported by fleshy core and innervated by the buccopharyngeal branch of the facial nerve; neurocranium with greatest width across nasal capsules; one facet and one condyle in the puboischiadic bar for articulating with the basipterygium; two intermediate segments between the basipterygium of the pelvic fin and the axial cartilage of the claspers; five terminal clasper cartilages; and posterior medial process of the puboischiadic bar absent. Cirrhigaleus asper is sister-species to a small clade comprising C. barbifer and C. australis which is supported by one synapomorphy, presence of conspicuous cusplets in the dermal denticles. Cirrhigaleus barbifer, C. asper and C. australis are redescribed herein and the neotype of C. barbifer is designated. A key to Cirrhigaleus species is also given and the inner relationships within Squalus is tentatively discussed.